Creating a source for cold, magnetically-trapped bromine atoms - Lam, J (2015)
This thesis demonstrates the feasibility of producing the ﬁrst cold source of halogen atoms, using Br atoms as the focus. Br atoms are produced by photodissociation of Br2, and detected by (2+1) REMPI and time-of-ﬂight measurements. Ground- and excited-state Br fragments are formed with a recoil velocity directed along the molecular beam axis. The excess energy from the dissociation laser provides the backscattered Br fragments with suﬃcient recoil velocity to match and cancel out the average velocity of the molecular beam. The Br fragments which undergo suﬃcient velocity cancellation remain in the laser detection volume for up to 5 ms. A magnetic trap, composed of two permanent bar magnets with their North poles facing each other, is placed around the detection volume and with an axis perpendicular to the molecular beam and laser axes. The centres of the trap and of the laser interaction volume are overlapped. The magnetic ﬁeld is linear near the centre of the trap and forms a 3-dimensional well with a depth of 0.22 T, equivalent to a trap depth of U0/kB = 255 mK, with the upper and lower standard error [215,325] mK, for ground-state Br. With this conﬁguration, Br atoms have been detected up to delays of 99 ms, to the next laser pulse, suggesting the possibility of accumulating density over successive molecular beam cycles. The decay of Br atoms from the trap is measured, and a Monte Carlo Markov Chain method is implemented to extract the intensity of the Br signal, which decreases to be on the order of the background noise at delays close to 99 ms. Monte-Carlo simulations demonstrate that the trap loss mechanisms are primarily due to collisions with the molecular beam and background gas, inhibiting the ability to accumulate trap density. These simulations also show that Majorana transitions to higher quantum states are minimal and can be ignored. Experimental measurements conﬁrm that near the peak of the molecular beam, when the strongest signal of Br is observed at long delays, around 60% of initially trapped Br atoms are lost due to molecular beam collisions, and (34 ±3)% due to collisions with the background gas. To minimise molecular beam collisions, a chopper construct is designed to reduce the beam pulse width and is placed between the molecular beam valve and detection volume. The chopper runs from 3,000 rpm to 80,000 rpm, during which the duration of the molecular beam at the detection volume is shortened from 130 μs (measured at the full width at half maximum) to between 80 μs and 13 μs, respectively. However, the chopper signiﬁcantly reduces the initial Br2 density in the trapping region, and the inﬂuence of the chopper construct in reducing molecular beam collisions requires further experimental work. Further work is also necessary to improve the operational components, such as reducing the base pressure in the detection chamber to lower background gas collisions, or using a heavier carrier gas to increase density of initially trapped Br atoms. These improvements can lead us closer toward building density of cold Br atoms in the trap over successive molecular beam cycles, with which a source of cold, dense halogen atoms can be realised.